Using genetic markers in unpedigreed populations to detect a heritable trait - Dodds, Ken G. (Zhejiang University Press, 2007)
Before a breeder invests selection pressure on a trait of interest, it needs to be established whether that trait is actually heritable. Some traits may not have been measured widely in pedigreed populations, for example, a disease or deformity may become more prevalent than previously, but is still relatively rare. One approach to detect inheritance would be to screen a commercial population to obtain a sample of “affecteds” (the test group) and to also obtain a random control group. These individuals are then genotyped with a set of genetic markers and the relationships between individuals within each group estimated. If the relatedness is higher in the test group than in the control group, this provides initial evidence for the trait being heritable. A power simulation shows that this approach is feasible with moderate resources.